Word, example and practice: learning and the learner in twelfth-century thought. Issue 5 (19th October 2020) - Sønnesyn, Sigbjørn Olsen
ABSTRACT: According to Bernard of Clairvaux, Hugh of Saint-Victor and John of Salisbury, it was only when knowledge was embodied in practice that its true meaning was revealed and could be understood. Yet, twelfth-century authors rarely offer any explanation for the inclusion of practice within the process of knowledge acquisition. This article explores why practice could be regarded as an irreducible component of twelfth-century pedagogies in light of both twelfth-century thought and the classical and patristic pedagogical thought they inherited, where the role and importance of practice is more explicitly expressed. Earlier thought provided the high Middle Ages with a conceptual basis for seeing active participation and practice on the part of the learner as integral to learning. Knowledge, on the view inherited by the twelfth century, could never fully be contained in words, whether written or spoken, but only in the re-enactive, self-reflective mind.